Colonisation of meiofauna: selectivity of substrates - Ramli, Rohayu; Kassim, Zaleha (TEXTROAD Publishing Corporation, 2016)
An ecological experiment was carried out in a remote estuarine creek of the Mengabang Telipot River (05°24.860”N,103°5.266”E). The introduced substrates were represented by the azoic sediment (AS), mixture of organic waste with azoic sediment (AS+OW) and the organic waste without the present of the azoic sediment (OW). A total of 25 bottles (with modified holes on the cap) filled with each of the introduced substrates were deposited and retrieved 1, 4, 7, 10 and 13 days post placement. The physico-chemical parameters of salinity, temperature, pH and dissolved oxygen were measured in situ. The results suggested that Gnathostomulida, Nematoda and Copepoda were colonising the introduced substrates with different rates according to their preference. The two-way ANOVA result also revealed that there is interaction between time and substrate effect on the density of all meiofaunal taxa except for the density of the gnatostomulids (p>0.05). The abilities of meiofauna to migrate either by infaunal burrowing or by active and passive transport creating the dynamics of colonisation pattern. Gnatostomulids have significant correlation with the salinity and only nematodes was significantly correlated with the pH values (p>0.05), which indirectly influenced the colonisation process on the introduced substrates. Unfavorable environmental condition, substrate characteristics, availability and quality of the food offered and behavior of individual taxa were identified as the important factors in determining the consistency of the new recruitment to survive, recolonise and therefore reproduce in the new substrate.